Dysbiosis of Oral and Gut Microbiomes in SARS-CoV-2 Infected Patients in Bangladesh: Elucidating the Role of Opportunistic Gut Microbes - Rafiqul Islam, S. M.; Foysal, Md. Javed; Hoque, M. Nazmul; Mehedi, H. M. Hamidullah; Rob, Md. Abdur; Salauddin, Asma; Tanzina, Afsana Yeasmin; Biswas, Sabuj; Noyon, Sajjad Hossain; Siddiki, A. M. A. M. Zonaed; Tay, Alfred; Mannan, Adnan (Frontiers in Medicine, 2022)
Coronavirus disease-2019 (COVID-19) is an infectious disease caused by SARS-CoV-2 virus. The microbes inhabiting the oral cavity and gut might play crucial roles in maintaining a favorable gut environment, and their relationship with SARS-CoV-2 infection susceptibility and severity is yet to be fully explored. This study investigates the diversity and species richness of gut and oral microbiota of patients with COVID-19, and their possible implications toward the severity of the patient's illness and clinical outcomes. Seventy-four (n = 74) clinical samples (gut and oral) were collected from 22 hospitalized patients with COVID-19 with various clinical conditions and 15 apparently healthy people (served as controls). This amplicon-based metagenomic sequencing study yielded 1,866,306 paired-end reads that were mapped to 21 phyla and 231 classified genera of bacteria. Alpha and beta diversity analyses revealed a distinct dysbiosis of the gut and oral microbial communities in patients with COVID-19, compared to healthy controls. We report that SARS-CoV-2 infection significantly reduced richness and evenness in the gut and oral microbiomes despite showing higher unique operational taxonomic units in the gut. The gut samples of the patients with COVID-19 included 46 opportunistic bacterial genera. Escherichia, Shigella, and Bacteroides were detected as the signature genera in the gut of patients with COVID-19 with diarrhea, whereas a relatively higher abundance of Streptococcus was found in patients with COVID-19 having breathing difficulties and sore throat (BDST). The patients with COVID-19 had a significantly lower abundance of Prevotella in the oral cavity, compared to healthy controls and patients with COVID-19 without diabetes, respectively. The altered metabolic pathways, including a reduction in biosynthesis capabilities of the gut and oral microbial consortia after SARS-CoV-2 infection, were also observed. The present study may, therefore, shed light on interactions of SARS-CoV-2 with resilient oral and gut microbes which might contribute toward developing microbiome-based diagnostics and therapeutics for this deadly pandemic disease.